Islamic Religious Education Teacher’s View and Learning Action on Puritan Fiqh in Madrasa - Rozi, Syaikhu; Yaqin, Ainul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
The objective of this research is to analyse the views, attitudes and approaches of PAI teachers in the teaching of fiqh materials in madrasas. The research was conducted using a qualitative approach based on a phenomenological research design. The data was collected through in-depth interviews with Fiqh teachers at Madrasah Aliyah. Moreover, the researchers employed the utilisation of documented textbooks utilised by the teaching staff. Additionally, questionnaires were distributed via Google Form. It was therefore concluded that the majority of Fiqh teachers in Mojokerto adhere to a moderate religious outlook. The teachers employed three distinct approaches in the teaching of puritan fiqh. Firstly, the contextual approach was assumed to be effective in fostering a moderate character and a liberal outlook in students. Secondly, the textual approach may result in students developing a fundamentalist perspective. Thirdly, the integration of textual and contextual approaches can influence students’ perspectives to be moderate based on wasathiyah principles. By having moderate views and attitudes and supported by the integration of contextual and textual approaches, a moderate perspective can be formed in students. Furthermore, this research rejected the hypothesis that Islamic Religious Education can create puritanical Islamic teaching. It also rejected the claim that the radicalisation process was carried out through madrasa.